2020
DOI: 10.1111/ijn.12872
|View full text |Cite
|
Sign up to set email alerts
|

How does patient provider communication affect patients' risk perception? A scenario experiment and an exploratory investigation

Abstract: Aim: The aim of the study was to examine whether patient-provider communication interacts with treatment outcomes to influence patients' risk perception. Background: Medical uncertainties and risks are among the most serious problems faced by patients. This is exacerbated by communication failure in patient-provider relationships and poor treatment outcomes. However, we do not know how communication and treatment outcomes shape patients' risk perception and concern about uncertainty. Design: The study is a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Narratives of patient experiences can inform patient-provider communication interventions by providing references for terminology commonly used and understood by patients. Additionally, prior studies have reported that the way a provider communicates modifies the patient’s perception of risk [ 46 ]. In our study, patients noted that reassurance from a provider that a condition was benign led to normalization of symptoms and reduced help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Narratives of patient experiences can inform patient-provider communication interventions by providing references for terminology commonly used and understood by patients. Additionally, prior studies have reported that the way a provider communicates modifies the patient’s perception of risk [ 46 ]. In our study, patients noted that reassurance from a provider that a condition was benign led to normalization of symptoms and reduced help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Literature examining social media in various surgical procedures advocates incorporating educational content into provider social media posts 22,23 . This could assuage such issues surrounding patient education through digestible and accessible material sourced directly from the health care team.…”
Section: Discussionmentioning
confidence: 99%
“…In order to better meet the situation of this study, the “individual” in the original scale was changed to the “medical staff.” Some items have been adjusted accordingly. “Most people, even those who are not close friends of this individual, trust and respect him/her as a coworker” was changed to “in the situational materials.” “Other work associates of mine who must interact with this individual consideration him/her to be trustworthy” was changed to “In the clinical materials, medical staff trust each other.” It has been debugged in other studies (Sun et al, 2020; Wei et al, 2020; X. N. Wu et al, 2016; X. N. Wu & Wu, 2015), two of which are in the medical environment. Cronbach's α coefficients of the revised Affective Trust subscale and Cognitive Trust subscale were .86 and .95, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to the risk measurement model, people's attitude to risk does not depend on the actual disaster degree of risk but on the degree of risk perception and acceptability (Cropanzano et al, 2008; Wildavsky & Dake, 1990). In the medical field, patients' acceptance of medical risk was defined as patients' (patient/family members/related persons) acceptance of something that may occur in the course of disease diagnosis and treatment (Sun et al, 2020; Wei et al, 2020). This acceptance of individual risk emphasizes that the acceptance is according to visual judgment and subjective perception with the effect of experience on cognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation